1986
DOI: 10.1097/00006250-198609000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Hemoglobin: A Sensitive Indicator of Gestational Diabetes

Abstract: Previous studies suggested that the assessment of hemoglobin A1 (HbA1) concentration was a poor indicator of diabetes in pregnancy. However, HbA1 was measured by ion exchange chromatography, which is subject to spurious alterations. To reevaluate the use of glycosylated hemoglobin concentration (GlyHb) as an indicator of gestational diabetes, 64 women at 10 to 15 weeks' gestation were studied by measuring GlyHb by a specific affinity chromatography assay, and blood glucose concentration was determined one hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Among women with diabetes in pregnancy, A1C at time of GDM diagnosis does appear to be associated with birthweight, 44,47,48 macrosomia, 38 and LGA 39,40 . In a retrospective cohort study of 357 women with GDM using the WHO criteria, Zawiejska et al 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Among women with diabetes in pregnancy, A1C at time of GDM diagnosis does appear to be associated with birthweight, 44,47,48 macrosomia, 38 and LGA 39,40 . In a retrospective cohort study of 357 women with GDM using the WHO criteria, Zawiejska et al 44 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Mor ris et al [10] in their study at 10-15 weeks of gestation concluded that HbAi by affinity chromatography may be a sensitive predictor of patients who will develop gesta tional diabetes. With a 1 SD threshold value, only 6.7% of the gestational diabetics would have missed diagnosis while 14.2% of the normal women would have been sub jected to further testing.…”
Section: Discussionmentioning
confidence: 86%
“…In a prenatal screening test for carbohydrate intolerance, Cousins et al [9] found that the 1-hour glucose challenge test (GCT) had greater specificity, sensitivity and predictive value for a positive diagnosis than the HbA] test. In contrast, Morris et al [10] reported that HbAi, determined by affinity chroma tography, may be used as a sensitive predictor of patients who will develop gestational diabetes during early preg nancy (10-15 weeks). Most reported studies were performed on Western populations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conclusions differ regarding the use of hemoglobin A 1c for such a test. In three studies, at threshold values selected to detect from 67% to 88% of gestational diabetic patients, the false-positive rates ranged from 25% to 65% [51][52][53]. The latter figures represent the proportion of the entire population who would require glucose tolerance testing because they exceed the designated hemoglobin A 1c value but who would be found not to have GDM.…”
Section: Glycated Proteinsmentioning
confidence: 99%